Isolation and partial characterization of an antigen-specific T-cell factor associated with the suppression of delayed type hypersensitivity. - Rosenstein, R W (1981)
Antigen-specific factors associated with immunosuppressive activity, released by cultured T cells from mice tolerant to the haptens trinitrophenyl, dinitrophenyl and oxazolone, were purified by hapten affinity chromatography. Their binding specificity for antigens paralleled their immunoregulatory activity. Like some immunoglobulin molecules, these factors had blocked NH2 termini and could be bound to Fc-like receptors on macrophages. However, neither immunoglobulin constant region determinants (isotypes) nor antigens encoded by the major histocompatibility complex were detected on the suppressive factors. The purified factors occurred as 68,000-dalton proteins and non-covalently linked dimers. No associated immunoglobulin light chain molecules were detected. The factors showed a marked propensity toward degradation with major breakdown products of 45,000-50,000 and 25,000-30,000 daltons. These results suggest that these molecules are the T-cell products analogous to B-cell immunoglobulin (equivalent to heavy chains) and that they may be the antigen-specific components which act in conjunction with major histocompatibility-controlled gene products to perform antigen-specific suppression.